DNA damage-induced AIM2 pyroptosis in high glucose-induced proximal tubular epithelial cell - Li, Lu’an; Zhang, Li; Cai, Yating; Li, Jiaying; Zheng, Siqi; Wang, Weiteng; Chen, Yinwen; Luo, Jieyi; Li, Ruizhao; Liang, Xinling (Frontiers in Cell and Developmental Biology, 2024)
Pyroptosis is one of the ways to cause proximal tubular epithelial cell death in diabetic nephropathy (DN), but the exact mechanism remains unclear. Absent in melanoma 2 (AIM2), a sensor for double-stranded DNA, creates an inflammasome that triggers the cleavage of gasdermin D (GSDMD), leading to a type of inflammatory cell death called pyroptosis. This study investigated the role of AIM2 in pyroptosis within proximal tubular epithelial cells in DN. We observed significantly elevated AIM2 expression in renal tubules from DN patients and db/db mice, as well as in high glucose (HG)-induced Human Kidney-2 (HK2) cells. Besides, increased AIM2 expression was accompanied by activation of the pyroptosis pathway (cleaved-caspase-1, GSDMD-FL, GSDMD-NT) in the renal cortex of db/db mice and HG-induced HK2 cells in vitro. Knocking down GSDMD can reduce HG-induced HK2 cell death, indicating that HG triggers pyroptosis in HK2 cells. Furthermore, HG-induced pyroptosis was mitigated in HK2 cells with AIM2 knockdown using siRNA. Additionally, reducing ROS levels using NAC was able to attenuate HG-induced HK2 cells DNA damage, AIM2 activation, and pyroptosis. Notably, AIM2 upregulation was observed in renal biopsies from DN patients, with expression levels positively correlating with serum creatinine and inversely with estimated glomerular filtration rate (eGFR). Collectively, DNA damage caused by HG could result in the activation of the AIM2 inflammasome, leading to the pyroptosis of proximal tubular epithelial cells, indicating that targeting AIM2 could be a potential novel approach for treating DN.